Omega-3 fatty acids for the prevention of myocardial infarction and arrhythmias - Pepe, Martino; Recchia, Fabio A (Cardiovascular Therapeutics, 2010)
In 1978, a report from the Chief Medical Officer in Greenland documented that coronary heart disease (CHD) was responsible for only 3.5% of all deaths in Greenland Eskimos [1], a strikingly small number compared to the typical figures found in the Western countries. Seeking potential explanations for such low frequency of cardiac events, investigators at the University of Aalborg, in Denmark, noted that the serum lipids of Eskimos was enriched in omega-3 fatty acids, that is, polyunsaturated fatty acids with the first double bond found in position 3 when the molecule is scanned from its methyl (-CH3) end (n-3 PUFA) [2,3]. They then identified fish oil as the primary source of n-3 PUFA in Eskimos’ diet [4], in particular eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), whose abundance in plasma and platelets has antihemostatic, hence antithrombotic effects [5]. These molecules consequently became the target of a wealth of studies aimed at explaining their preventive effects against cardiovascular diseases.